2019
DOI: 10.1080/13543784.2019.1655539
|View full text |Cite
|
Sign up to set email alerts
|

An update of SGLT1 and SGLT2 inhibitors in early phase diabetes-type 2 clinical trials

Abstract: Introduction: More than 424 million adults have diabetes mellitus (DM). This number is expected to increase to 626 million by 2045. The majority (90-95%) of people with DM has type 2-diabetes (T2DM). The continued prevalence of DM and associated complications has prompted investigators to find new therapies. One of the most recent additions to the antidiabetic armamentarium are inhibitors of sodium-glucose co-transporters 1 and 2 (SGLT1, SGLT2). Areas covered: The authors review the status of SGLT2 inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…liraglutide, exenatide, albiglutide) [30,31], and the newly approved SGLT inhibitors (e.g. canagliflozin, dapagliflozin, empagliflozin) [32].…”
Section: Management Of Dmmentioning
confidence: 99%
See 3 more Smart Citations
“…liraglutide, exenatide, albiglutide) [30,31], and the newly approved SGLT inhibitors (e.g. canagliflozin, dapagliflozin, empagliflozin) [32].…”
Section: Management Of Dmmentioning
confidence: 99%
“…Many clinical trials have reported that SGLT2i either alone or with GLP-1RA has a potent cardioprotective effect and safety even in DM patients with previous CVD [32,59]. Large clinical trials including the CREDENCE clearly showed the benefit of SGLT2i in the amelioration of cardiovascular risks in diabetic patients [60].…”
Section: Sglt Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another interesting review article, Kanasaki et al analyzes distinct molecular mechanisms of autophagy regulation by glucagon, GLP-1, and DPP-4 inhibitor. In addition, they also discuss the potential contribution of these regulatory pathways in the induction of beneficial autophagy-upon bariatric surgery, which have implications in the treatment of diabetic diseases (Adeghate et al, 2019).…”
mentioning
confidence: 99%